Unveiling Similes in Olivia Rodrigo's GUTS: Crafting Emotional Narratives through Lyrics: English - siti14 jamila; Ahmad Yusuf Firdaus; Dwi Taurina Mila Wardhani (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2025)
This study examined the types and meanings of Numerous similes in Olivia Rodrigo's album Guts song lyrics. Similes, which create direct comparisons between two things using words like